Investigating the effect of immunomagnetic separation on the immunophenotype and viability of plasma cells in plasma cell disorders - Ágnes Czeti; Soma Sashalmi; Ferenc Takács; Gábor Szalóki; Csilla Kriston; Gergely Varga; Péter Farkas; Aryan Hamed; Ágnes Márk; Gábor Barna (Frontiers Media S.A., 2024)
Plasma cell enrichment plays a pivotal role in the accurate prognosis and molecular characterization of multiple myeloma. The separation is commonly carried out by positive cell selection using CD138 monoclonal antibody conjugated to magnetic beads. Optimally, during the separation procedure, the cells should neither be damaged, nor should their phenotype be significantly altered, as these changes would falsify the results if the isolated cells were subsequently used. For this reason, we investigated the expression patterns of different surface markers by flow cytometry before and after magnetic isolation using bone marrow or peripheral blood samples from 12 patients with plasma cell disorders. The selected markers are not only used as backbone markers in routine diagnostics (CD19, CD38, CD45, CD117, and CD138), but they also play an important role in cell adhesion and connection with microenvironment (CD44, CD49d, CD56, and CD81) or possibly drug resistance (CD69, CD86, and CD184), making them promising targets for myeloma research. Moreover, we examined the effects of separation on cell viability in 8 cases. The intensities of 8 out of the 12 investigated markers were slightly influenced, while CD138, CD38, CD56, and CD184 were changed significantly, however the immunophenotype of the cells was not changed. Positive markers remained positive and negative ones remained negative after the separation procedure. In addition, the number of apoptotic plasma cells was significantly reduced during separation, facilitating further examination of the cells. Our results showed that magnetic isolation can be considered as a reliable option but the immunophenotype of plasma cells should be validated after the separation if the intensities of the markers are important for further experiments.